2013
DOI: 10.13080/z-a.2013.100.041
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of spring barley (Hordeum vulgare L.) screening methods for Fusarium head blight resistance breeding

Abstract: Fusarium head blight (FHB) is a widespread disease of cereals, including barley (Hordeum vulgare L.), that causes substantial grain yield losses and grain quality deterioration. Resistant varieties provide the greatest potential for reducing FHB. In the present study, we adapted two methods for screening FHB severity using Fusarium culmorum. We used a cut-spike method and a spray inoculation method in the field conditions for screening different spring barley genotypes of Latvian and foreign origin. Screening … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 26 publications
0
8
0
1
Order By: Relevance
“…had been most frequently isolated. These fungi can cause Fusarium head blight (FHB) and produce mycotoxins [6,7].…”
mentioning
confidence: 99%
“…had been most frequently isolated. These fungi can cause Fusarium head blight (FHB) and produce mycotoxins [6,7].…”
mentioning
confidence: 99%
“…During our investigation, DHA was found to be of particularly importance as a useful complement to growth chamber and field screening because of contradictory findings reported previously on barley plants (Han and Kim, 2005;Usele et al, 2013). DHA was selected on basis of its similarity to adult barley spike and spikelet inoculations using head and floret techniques for Type I and Type II resistance, respectively.…”
Section: Discussionmentioning
confidence: 95%
“…Han and Kim (2005) found statistically significant correlation between DHA and point inoculation (Type II resistance) in growth chambers where all biotic and abiotic conditions were strictly controlled. On the contrary, another research that was based on a set of five-year data, showed significant differences in the FHB severity of different plant materials by applying DHA and field inoculation methods (Usele et al, 2013). Despite the importance of DHA, there are no associated reports on the aggressiveness of diverse Fusarium isolates or species.…”
Section: Introductionmentioning
confidence: 99%
“…This is best studied for the pathogens of the Fusarium head blight (FHB) complex on wheat, where crop residues constitute the principal source of inoculum in the fi eld [5,6]. Fusarium graminearum predominates in Central and southeastern Europe, while in cooler maritime climates mainly F. culmorum, F. avenaceum, F. poae, and Microdochium species occur [7].…”
Section: Introductionmentioning
confidence: 99%